الاصلاحات السياسية في بايلك الشرق الجزائري على عهد صالح باي 1771-1792م - نادية سنوساوي (جامعة محمد بوضياف بالمسيلة, 2025)
تناولنا في هذه الدراسة الاصلاحات السياسية في بايلك الشرق الجزائري على عهد صالح باي 1771_1792 م والتي تتمحور اشكاليتها: فيما تمثلت الاصلاحات السياسية التي قام بها صالح باي في بايلك الشرق الجزائري؟ ولعل اهم المصادر المعتمد عليها في هذه الدراسة هي اطروحة الدكتوراه لفاطمة الزهراء قشي المعنونة ب قسنطينة في ع صالح باي البايات وكتاب ابن العنتري محمد صالح، تاريخ قسنطينة. ومن خلال هذه المصادر استطعنا تقسيم هذا العمل الى ثلاثة فصول بدأنا دراستنا بفصل تمهيدي لاوضاع بايلك الشرق الجزائري قبل 1771م اما الفصل الاول معنون بنبذة عن شخصية صالح باي اما الفصل الثاني فتناولنا الاصلاحات السياسية لصالح باي واثرها على البايلك ومن بين اهم النتائج المتوصل اليها في هذه الدراسة ان صالح باي هو احد بايات الشرق الجزائري كانت فترة حكمه بين 1771/1792م دام حكمه حوالي 20 سنة عرفت المنطقة خلال حكمه انجازات كبيرة سياسيا وعسكريا وحتى قضائيا واجتماعيا مما زاد ولاء الاهالي له في نهاية حكمه ظهر معارضون وخصوم كثيرون ضده مما ادى الى تخطيط الباشا لعزله فكانت فترة حكمه منعطفا حاسما في تاريخ قسنطينة Summary: This study examined the political reforms in the Eastern Beylik of Algeria during the reign of Salah Bey (1771-1792 AD). The problem statement of this study revolves around the political reforms implemented by Salah Bey in the Eastern Beylik of Algeria?. One of the primary sources relied upon in this study is the Ph.D. thesis of Fatima Zahra Gachi, titled "Constantine during the era of Salah Bey the Beys," and the book "The History of Constantine" by Ibn al-Antari Muhammad Salah. Based on these sources, we were able to divide this work into three chapters. We began our study with an introductory chapter on the situation of the Eastern Beylik of Algeria before 1771 AD. The first chapter is titled "A brief overview of Salah Bey's personality," while the second chapter discusses the political reforms of Salah Bey and their impact on the beylik. Among the key findings of this study is that Salah Bey was one of the Beys of Eastern Algeria, whose reign lasted from 1771 to 1792 AD, spanning around 20 years. During his rule, the region witnessed significant achievements in politics, military, judiciary, and social aspects, which increased the loyalty of the people towards him. However, towards the end of his reign, many opponents and adversaries emerged against him, leading the Pasha to plot his removal. His reign marked a decisive turning point in the history of Constantine.